Respiratory syncytial virus and airway microbiota – A complex interplay and its reflection on morbidity. Issue 6 (7th May 2021) - Rossi, Giovanni A.; Ballarini, Stefania; Silvestri, Michela; Sacco, Oliviero; Colin, Andrew A.
Abstract: The immunopathology of respiratory syncytial virus (RSV) infection varies considerably, severe disease occurring only in a minority of the affected children. The variability of the clinical presentation is in part explained by viral and environmental factors but, in infants and young children, disease severity is certainly linked to the physiologic immaturity of the innate and adaptive immune system. There is evidence that the maturation of the host immune response is positively influenced by the composition of the nasopharyngeal microbiome that, promoting an efficient reaction, can counteract the predisposition to develop viral respiratory infections and lower the risk of disease severity. However, interaction between the nasopharyngeal microbiota and respiratory viruses can be bidirectional since microbial dysbiosis may also represent a reflection of the disease‐induced alterations of the local milieu. Moreover, viruses like RSV can also increase the virulence of potential pathogens in nasopharynx, a main reservoir of bacteria, and therefore promote their spread to the lower airways causing superinfection. Moreover, if negative changes in microbial community composition in early life may constitute a heightened risk toward severe RSV respiratory infection, on the contrary specific groups of microorganisms seem to be associated with protection. A better understanding into the potential negative and positive role of the different nasopharyngeal bacterial species on RSV infection may improve primary prevention and possibly care of this highly contagious disorder.